Vacancies and sea urchin structure protect cobalt manganese spinel from anion poisoning in peroxymonosulfate activation - Hui Jia; Rumeng Liu; Tenglong Huang; Fulin Wang; Shanshan Dong; Huihui Dai; Zhenxing Zeng; Dingding Tang; Xiaodong Wang; Suhua Chen (npj Clean Water)
Abstract Peroxymonosulfate (PMS) activation by cobalt manganese spinel (Co-Mn) is always unsatisfactory due to the interference of co-existing anions in water. In this study, we used a sulfate-modification strategy to prepare a sea urchin-like Co-Mn catalyst (CoMn2O4-S) with abundant oxygen vacancies for counteracting the interference of anions in pollutant degradation. Compared with the conventional Co-Mn catalyst (CoMn2O4), CoMn2O4-S exhibited higher resistance to poisoning of NO3 −, Cl−, and SO4 2− in PMS activation involved phenol degradation. Additionally, H2PO4 − could even enhance phenol degradation by 150.2% for CoMn2O4-S/PMS system, in contrast to its induced 18.5% inhibition to CoMn2O4/PMS system. It was demonstrated that vacancies and sea urchin structure alleviated catalyst agglomeration for preserving catalytic sites and promoted catalyst surface modulation for radical diffusion, contributing to the enhanced stability in saline water. This work provides a facile strategy for overcoming the negative effects of co-existing anions on heterogeneous PMS-activation based water treatment.